REORIENTASI PENDIDIKAN ISLAM - Siswanto, Siswanto (JURNAL TADRIS STAIN PAMEKASAN, 2010)
Abstract: There are two principal reasons for the need to reorient an islamic education in Indonesia to strengthen civil society discourse. The first, the concept of an islamic education and practices are deemed too narrow, too much emphasis on the interests of the hereafter. The second, institutions of islamic education  has not been able, or less, to meet the needs of the muslims to face the challenges  in the modern world. Therefore, educational reform efforts can be directed steadily, if only based on some strategies and steps: reorientation of the basic philosophical and theoretical framework of education, vision and mission of islamic education, islamic educational strategies, islamic educational goals, islamic educational curriculum, islamic educational methodologies, and  management and resources of  islamic education.